1997
DOI: 10.3109/03009739709178940
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of Sleep Habits and Sleeping Difficulties in an Elderly Swedish Population

Abstract: A random sample of 876 subjects aged 65-79 years were investigated by means of a questionnaire concerning sleep and related factors. Sleep problems were reported by 23.8% of females and 13.3% of males.Moderate or major complaints of maintaining sleep were reported by 43.5% of subjects, early morning awakening 33.4% and difficulties falling asleep 31.4%. Daytime sleepiness was more common among males, and a relationship between daytime sleepiness and perceived poor sleep was found. Daytime napping was common, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
52
4
1

Year Published

1999
1999
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(60 citation statements)
references
References 19 publications
(14 reference statements)
3
52
4
1
Order By: Relevance
“…This study is consistent with the study conducted in Egypt which reported that prevalence of insomnia among elderly was 36.4% [13] Similar study conducted in Italy also reported that 36.7% of the respondents had insomnia [14] and another study conducted in Iran revealed that 39.2% had insomnia [9] and a study in North India identified that 32% had insomnia [8]. But the present study is contrary with the study conducted in Sweden which yielded that 13.3% reported insomnia [5].…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…This study is consistent with the study conducted in Egypt which reported that prevalence of insomnia among elderly was 36.4% [13] Similar study conducted in Italy also reported that 36.7% of the respondents had insomnia [14] and another study conducted in Iran revealed that 39.2% had insomnia [9] and a study in North India identified that 32% had insomnia [8]. But the present study is contrary with the study conducted in Sweden which yielded that 13.3% reported insomnia [5].…”
Section: Discussioncontrasting
confidence: 55%
“…Similarly, a study in Sweden reported that 23.8% of female and 13.3% of male complained of sleep problems among elderly which showed that insomnia is more prevalent among female than male. Among them, 43.5% reported Early Morning Awakening (EMA) and 33.4% reported difficulty maintaining sleep (DMS) [4,5]. Numerous studies have indicated that up to 50% of European individuals aged 60+ years' experience insomnia.…”
Section: Introductionmentioning
confidence: 99%
“…Since the study population was young adults attending a university, effects of age on sleep disturbances could not be found. Like in many studies showing that sleep disturbances are found more frequently among women than men (7)(8)(9)(10)(11)(12), it was found in this study that the female students slept slightly shorter and reported more sleep disturbances than their male counterparts.…”
Section: Discussionmentioning
confidence: 46%
“…During stress, the central nervous system and peripheral functions are generally altered to re-establish homeostasis and to preserve life. Complaints about too little sleep, and difficulties initiating and maintaining sleep were more prevalent in this study than are reported in the general Swedish population (Liljenberg et al 1988, Gislason & Almqvist 1987 and among the elderly (Mallon & Hetta 1997) using the USI questionnaire. The proportion of too little sleep corresponds with Simpson and Lee´s (1996) results, but is less prevalent than that reported by Magni et al (1987) in men and women prior to cardiac valve replacements and CABG.…”
Section: Reported and Polysomnographically Determined Sleep Before Cabgcontrasting
confidence: 51%
“…Twenty-two patients (50%) in the present study had combined sleep problems. This corresponds with results reported prior to MI and/or major depression (Carney et al 1990), after MI in rehabilitation (Hyyppä & Kronholm 1989), among elderly men with angina pectoris and arrhythmia (Asplund 1994), and in subjects with a chronic disease with severe insomnia and/or depression (Katz & McHorney 1998 We found that one third of the patients had a moderate or higher degree of physical tiredness and not being refreshed by sleep, which is higher than has been reported in Swedish epidemiological studies (Mallon & Hetta 1997, Liljenberg et al 1988, Broman et al 1996. This was in line with findings (22 % to 39 %) reported in patients about to undergo CABG (Eriksson 1988, King & Parrinello 1988.…”
Section: Reported and Polysomnographically Determined Sleep Before Cabgcontrasting
confidence: 44%